CLINICAL-NEUROLOGICAL STRUCTURE OF NERVOUS SYSTEM INJURIES IN PATIENTS SUFFERING WITH COVID -19 - Raxmatullaeva G.Q., Toxirov J. J. (Galaxy International Interdisciplinary Research Journal, 2023)
Currently, the coronavirus (COVID-19) pandemic is an urgent problem for all countries of the world. Like all countries, the incidence of this virus is increasing in our republic, and new clinical features are being observed. Observations show that the disease affects all body systems and leaves its obvious complications. In particular, it causes various pathological symptoms and syndromes of the central and peripheral nervous systems.